FACTORS INFLUENCING AN EFL LEARNER’S PROFICIENCY: AN ENGLISH TEACHER’S PERSPECTIVE - Pariyanto Pariyanto; Bramatya Pradipta (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2019)
This study investigated the factors affecting an EFL learner's success in learning English. An experienced English teacher was chosen as a model of a successful learner of English and was interviewed on how she learned English. The findings indicate that the factors contributing to her success in learning English include (1) internal motivation, (2) social context, and (3) a positive attitude towards English. The findings of this study are in line with second language learning theories. This implies that such factors as motivation, social context, and positive attitude towards target language need to be taken into account to succeed in learning English as a foreign language.